Astrocytic Acid-Sensing Ion Channel 1a Contributes to the Development of Epileptic Cognitive Impairment - Wen Li; Huimin Zhou; Xiaona Li; Gengyao Hu; Dong Wei (Biomolecules)
Reactive astrogliosis and acidosis, common features of epileptogenic lesions, express a high level of astrocytic acid-sensing ion channel-1a (ASIC1a), a proton-gated cation channel and key mediator of responses to neuronal injury. This study investigates the role of astrocytic ASIC1a in cognitive impairment following epilepsy. Status epilepticus (SE) in C57/BL6 mice was induced using lithium–pilocarpine; the impact of ASIC1a on astrocytes was assessed using rAAV–ASIC1a–NC and rAAV–ASIC1a–shRNA, injected in the CA3 region of mice. Behavioral assessments were conducted using the Morris water maze (MWM). Western blotting and immunofluorescence were applied to evaluate ASIC1a and Gfap expression while analyzing intracellular calcium and extracellular glutamate (Glu) concentrations in primary cultured astrocytes isolated from the brains of 1 to 3-day-old mice and treated LPS. Results showed enhanced astrocyte proliferation and ASIC1a expression in the dentate gyrus of epileptic mice 7, 21, and 28 days post-SE (all p < 0.05). Escape latency in the MWM further suggested that ASIC1a regulates cognitive function in mice with chronic epilepsy. LPS stimulation in vitro mimicked inflammatory responses, increasing ASIC1a after 24 h, which increased the concentration of intracellular calcium and extracellular expression of Glu; inhibition of ASIC1a expression reversed this process. To sum up, these data confirm that astrocytic ASIC1a may facilitate cognitive dysfunction post-epilepsy, presenting a potential therapeutic target.